The Realization of Religious Culture Through the Implementation of the SKUA Program Based on Persuasive Strategies in Madrasah Ibtida’iyah - Bahrodin, Ariga; Kibtiyah, Asriana; Qomariyah, Lailatul; Rofi’ah, Siti; Widiyati, Evita; Mahsun, Ali (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The purpose of this study was to determine the implementation of the SKUA program based on persuasive strategy to realize a religious culture at MI Darussalam Badang Jombang. The research method used was descriptive qualitative, because the purpose of the study was to find data that was natural setting where the conditions studied were in accordance with the conditions in the field. The findings in this study in the implementation of the SKUA program based on persuasive strategy include the habituation of applying the materials contained in the SKUA program provided by educators and students not only apply them at school but also in everyday life. In addition, good role models in behavior and attitude are also shown by educators so that students imitate and apply them.  Future research can focus on analyzing the long-term effectiveness of the SKUA program based on persuasive strategy in shaping students' religious culture, both within the school environment and in their daily lives. A longitudinal approach can be employed to observe changes in students' attitudes and behaviors over a certain period, allowing for an assessment of the extent to which religious values are internalized sustainably. Furthermore, the study can expand its scope by comparing the implementation of the SKUA program across multiple educational institutions to identify factors influencing its success. This comparative study approach will provide broader insights into the effectiveness of persuasive strategy methods in fostering religious culture in various educational contexts.